PELATIHAN PENGGUNAAN MICROSOFTT OFFICE WORD, POWERPOINT, EXCEL 2010 DAN GMAIL DI SMA ARASTAMAR AIR UPAS - Aswan Aswan (Jurnal PKM Setiadharma, 2023)
SMA Arastamar is the only high school currently in the Air Upas area, Air Upas District, Ketapang Regency, West Kalimantan. In this area SMA Arastamar was founded by the Servant of God. This high school is under the SABAS Foundation. The presence of this school is to improve human resources in the region. Based on the results of observations made to class XII science and social studies students, there were students who were less active in carrying out their duties. This happened because the learning process transmigrated into distance learning or better known as PJJ as a result of Covid-19. Covid-19 and forcing students to be able to use computer technology properly and correctly. Making assignments that had to be made in Office Word, PowerPoint and Excel did not go well, due to the lack of understanding of children in operating these devices, and not only that, students also had to be able to use Gmail to send assignments that were There is. With the existing observations, the authors are encouraged to conduct community service training for class XII students majoring in Science and Social Studies at Arastamar High School in order to improve the quality of students in information technology-based education.